2004
DOI: 10.1046/j.1474-919x.2004.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Offspring sex ratio variation in relation to brood size and mortality in a promiscuous species: the Aquatic Warbler Acrocephalus paludicola

Abstract: We analyse nestling sex ratio variation in the Aquatic Warbler Acrocephalus paludicola to test for predictions from sex allocation theory that the brood sex ratio is close to parity. We also tested Fiala's (1980) prediction that there is no difference in sex ratio between broods affected and not affected by mortality, and whether a shift in primary sex ratios or simple differential mortality by sex underlies that difference. Furthermore, we explore additional analytical possibilities for inferring proximate me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…Such male biased hatching failure has been recently shown in a study of a natural population of tree swallows Tachycineta bicolor (Whittingham and Dunn 2001), and in captive zebra finches Taenopygia guttata (Rutkowska and Cichoń 2002). The diverging sex ratio between complete and partial broods was also reported in aquatic warbler Acrocephalus paludicola (Dyrcz et al 2004), but sex biased embryo mortality was not found in studies of sparrowhawk Accipiter nisus (van den Burg et al 2002). There is also some evidence that prenatal mortality is male‐biased in a variety of mammal species (Clutton‐Brock 1991, for review).…”
Section: Discussionmentioning
confidence: 66%
“…Such male biased hatching failure has been recently shown in a study of a natural population of tree swallows Tachycineta bicolor (Whittingham and Dunn 2001), and in captive zebra finches Taenopygia guttata (Rutkowska and Cichoń 2002). The diverging sex ratio between complete and partial broods was also reported in aquatic warbler Acrocephalus paludicola (Dyrcz et al 2004), but sex biased embryo mortality was not found in studies of sparrowhawk Accipiter nisus (van den Burg et al 2002). There is also some evidence that prenatal mortality is male‐biased in a variety of mammal species (Clutton‐Brock 1991, for review).…”
Section: Discussionmentioning
confidence: 66%
“…2006). All these factors are interrelated, and it is not yet clear whether skewed offspring sex ratios are adaptive, or what their proximate or ultimate drivers are (Weatherhead & Teather 1991, Sheldon 1998, Dyrcz et al . 2004, Ewen et al .…”
Section: Results and Reviewmentioning
confidence: 99%
“…1996, Griffith et al . 2003, clutch size (Dyrcz et al . 2004), age at first breeding , postnatal dispersal patterns (Gowaty 1993, Julliard 2000, the presence or contribution of nest helpers or brood parasites (Komdeur 1998, Legge et al .…”
Section: Offspring Sex Ratiosmentioning
confidence: 99%
“…In birds, brood sex ratio can be biased in response to environmental conditions (Oddie 2000; Suorsa et al . 2003; Dyrcz et al . 2004; Szekely et al .…”
Section: Discussionmentioning
confidence: 99%